2017
DOI: 10.1038/srep40515
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter cinaedi antigen CAIP participates in atherosclerotic inflammation by promoting the differentiation of macrophages in foam cells

Abstract: Recent studies have shown that certain specific microbial infections participate in atherosclerosis by inducing inflammation and immune reactions, but how the pathogens implicated in this pathology trigger the host responses remains unknown. In this study we show that Helicobacter cinaedi (Hc) is a human pathogen linked to atherosclerosis development since at least 27% of sera from atherosclerotic patients specifically recognize a protein of the Hc proteome, that we named Cinaedi Atherosclerosis Inflammatory P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The major antiphagocytic activity mediated by TFSS was characterised as VirB7, a key component of T pilus filament, and the VirB11 ATPase. In addition, the cinaedi atherosclerosis inflammatory protein from Helicobacter cinaedi has been found to promote the differentiation of the pro-inflammatory profile of macrophages, triggering the formation of foam cells, which are important for the genesis of atherosclerotic plaques (D'Elios et al, 2017). The results revealed that C. pneumoniae phospholipase D is able to drive the expression of pro-inflammatory cytokines to activate a Th17 immune response that plays a crucial role in the development of atherosclerosis.…”
Section: Impairment Of Autophagosome Formation Reduces Helicobactermentioning
confidence: 97%
See 1 more Smart Citation
“…The major antiphagocytic activity mediated by TFSS was characterised as VirB7, a key component of T pilus filament, and the VirB11 ATPase. In addition, the cinaedi atherosclerosis inflammatory protein from Helicobacter cinaedi has been found to promote the differentiation of the pro-inflammatory profile of macrophages, triggering the formation of foam cells, which are important for the genesis of atherosclerotic plaques (D'Elios et al, 2017). The results revealed that C. pneumoniae phospholipase D is able to drive the expression of pro-inflammatory cytokines to activate a Th17 immune response that plays a crucial role in the development of atherosclerosis.…”
Section: Impairment Of Autophagosome Formation Reduces Helicobactermentioning
confidence: 97%
“…The results revealed that C. pneumoniae phospholipase D is able to drive the expression of pro-inflammatory cytokines to activate a Th17 immune response that plays a crucial role in the development of atherosclerosis. In addition, the cinaedi atherosclerosis inflammatory protein from Helicobacter cinaedi has been found to promote the differentiation of the pro-inflammatory profile of macrophages, triggering the formation of foam cells, which are important for the genesis of atherosclerotic plaques(D'Elios et al, 2017). Of note, H. pylori DNA was detected in atherosclerotic plaques, suggesting the association of H. pylori with the pathogenesis of atherogenesis(Kaplan et al, 2006).…”
mentioning
confidence: 99%
“…Monocytes derived from buffy coats were prepared as described previously (51). For macrophage differentiation, 5 × 10 5 monocytes, seeded in 24-well plates, were cultured in RPMI 1640 medium (Euroclone), 20% FBS, 4 mM HEPES (Gibco, ThermoFisher Scientific), and 50 µg/ml gentamycin (Gibco, ThermoFisher Scientific) in the presence of 100 ng/ml M-CSF (Miltenyi Biotec) for a 6-day differentiation.…”
Section: Cell Cultures Monocyte Isolation Macrophage Differentiationmentioning
confidence: 99%
“…A 54‐year‐old immunocompetent Japanese man who was found to have bacteremia complicated with bilateral lower extremity cellulitis due to H. cinaedi had two recurring episodes post‐treatment; therefore, treatment was prolonged (12 weeks) until his symptoms subsided . The H. cinaedi cinaedi atherosclerosis inflammatory protein (CAIP) antigen participates in atherosclerotic inflammation by promoting macrophage differentiation into foam cells and drives a pro‐inflammatory Th1 phenotype, an immunopathological response associated with atherosclerosis . Schmitz et al .…”
Section: Taxonomy Prevalence and Diagnosis Of Non‐helicobacter Pylomentioning
confidence: 99%
“…25 The H. cinaedi cinaedi atherosclerosis inflammatory protein (CAIP) antigen participates in atherosclerotic inflammation by promoting macrophage differentiation into foam cells and drives a pro-inflammatory Th1 phenotype, an immunopathological response associated with atherosclerosis. 26 Schmitz et al 27 showed that in vitro growth of H. cinaedi although not up to the species level. Fernandez-Flores et al 31 demonstrated that an anti-Treponema antibody also stains gastric NHPH.…”
Section: Taxonomy Prevalence and Diagnosis Of Non-helicobacter Pymentioning
confidence: 99%